Answer:
Multiply the first equation by 3 and multiply the second equation by -2.
This is justified by the multiplication property of equality
Explanation:
we have
----> first equation
----> second equation
step 1
Multiple the first equation by 3 both sides
-----> by multiplication property of equality
----> new first equation
step 2
Multiple the second equation by -2 both sides
-----> by multiplication property of equality
----> new second equation
step 3
Solve the system of equations by elimination
Adds new first equation and new second equation
Find the value of x
substitute the value of y in any equation and solve for x
The solution is the point
therefore
Multiply the first equation by 3 and multiply the second equation by -2.
This is justified by the multiplication property of equality